Methodology for evaluating the social intelligence of a coach - Smoldovskaya I.O.; Krasavtseva E.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was the development and psychometric analysis of the "Social intelligence of a coach" methodology. Methods and structure of the study. The sample consisted of 120 coaches (78 men and 42 women, aged from 21 to 65 years), various sports; 98 students of 8 specializations of SSUS in Smolensk and 45 sports psychologists. A correlation analysis, confirmatory factor analysis, and testing of psychometric indicators were carried out: representativeness, reliability, convergent and divergent validity. Competitive validity was determined using tests: verbal intelligence (J. Barrett), non-verbal intelligence (Ravena), multiple intelligence: spatial-visual, interpersonal, intrapersonal (G. Gardner). Results and conclusions. 4 subscales of the trainer’s social intelligence were empirically verified, and norms for the expression of each ability were determined. Examples of the content of the methodology tasks are illustrated. The developed methodology “Social intelligence of a coach” is reliable and valid, and can be proposed for scientific and practical use in sports practice with the possibility of extrapolation for the diagnosis of athletes, judges, and parents.